Exploring the Effects of Bone Marrow Mesenchymal Stem Cells on Amyloid Plaque Reduction in a Rat Model of Alzheimer's Disease - Annita Annita; Gusti Revilla; Hirowati Ali; Almurdi Almurdi (Faculty of Medicine, Universitas Andalas, 2023)
Objective: This study aimed to evaluate the therapeutic potential of Bone Marrow-derived Mesenchymal Stem Cells (BM-MSCs) in mitigating amyloid plaque formation in Alzheimer's disease induced by Aluminum Chloride (AlCl3) in rats. Methods: Rats were divided into three groups: negative control, positive control (AlCl3-induced), and treatment (AlCl3 + BM-MSCs). Cognitive function was assessed five days post-induction, and amyloid plaques were quantified using Congo Red staining in the cortex and hippocampus. Results: A significant reduction in amyloid plaque was observed in rats treated with BM-MSCs. The proportion of stained areas decreased from 1.88 to 1.73 in the cortex and from 1.61 to 1.47 in the hippocampus, compared to AlCl3-only controls. Conclusion: BM-MSCs demonstrated a moderate but statistically significant reduction in amyloid plaque in a rat model of Alzheimer's disease, indicating their therapeutic potential.